The two faces of titanium dioxide nanoparticles bio-camouflage in 3D bone spheroids - Souza, W.; Piperni, S. G.; Laviola, P.; Rossi, A. L.; Rossi, Maria Isabel D.; Archanjo, Braulio S.; Leite, P. E.; Fernandes, M. H.; Rocha, L. A. [UNESP]; Granjeiro, J. M.; Ribeiro, A. R. (Nature Publishing Group, 2019)
Titanium (Ti) and its alloys are widely used in dental implants and hip-prostheses due to their excellent biocompatibility. Growing evidence support that surface degradation due to corrosion and wear processes, contribute to implant failure, since the release of metallic ions and wear particles generate local tissue reactions (peri-implant inflammatory reactions). The generated ions and wear debris (particles at the micron and nanoscale) stay, in a first moment, at the interface implant-bone. However, depending on their size, they can enter blood circulation possibly contributing to systemic reactions and toxicities. Most of the nanotoxicological studies with titanium dioxide nanoparticles (TiO(2)NPs) use conventional two-dimensional cell culture monolayers to explore macrophage and monocyte activation, where limited information regarding bone cells is available. Recently threedimensional models have been gaining prominence since they present a greater anatomical and physiological relevance. Taking this into consideration, in this work we developed a human osteoblastlike spheroid model, which closely mimics bone cell-cell interactions, providing a more realistic scenario for nanotoxicological studies. The treatment of spheroids with different concentrations ofTiO(2)NPs during 72 h did not change their viability significantly. Though, higher concentrations ofTiO(2)NPs influenced osteoblast cell cycle without interfering in their ability to differentiate and mineralize. For higher concentration ofTiO(2)NPs, collagen deposition and pro-inflammatory cytokine, chemokine and growth factor secretion (involved in osteolysis and bone homeostasis) increased. These results raise the possible use of this model in nanotoxicological studies of osseointegrated devices and demonstrate a possible therapeutic potential of this TiO(2)NPs to prevent or reverse bone resorption.